Health disparities in rheumatoid arthritis. (November 2022) - Ciofoaia, Elena I.; Pillarisetty, Anjani; Constantinescu, Florina
Rheumatoid arthritis (RA) is an autoimmune disease characterized by joint inflammation that involves symmetric polyarthritis of small and large joints. Autoimmune rheumatic diseases represent a significant socioeconomic burden as they are among the leading causes of death and morbidity due to increased risk of cardiovascular disease. Health disparities in patients with rheumatoid arthritis affect outcomes, prognosis, and management of the disease.